2018
DOI: 10.1177/0094582x18757473
|View full text |Cite
|
Sign up to set email alerts
|

Hall of Mirrors: Media, Democratization, and the Public Sphere in Maranhão, Brazil

Abstract: Freedom of expression and access to diverse sources of information are seen as critical elements of democracy, although their concretization on the ground is subject to strong interference. Recent regime change in Maranhão, one of Brazil’s poorest states, has led to the emergence of new media and some expansion of the public sphere. The traditional oligarchy continues to dominate the media, however, and the opposition media replicate its exclusion of nonelite actors. The Maranhão experience confirms that norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the wake of this subnational turn, scholars have identified pockets of democracy in authoritarian countries (Gilley, 2010) and pockets of authoritarianism in democratic countries (Benton, 2017;Durazo Herrmann, 2010;Giraudy, 2015;Sidel, 2014). Moreover, they have analyzed the democratization of subnational authoritarian enclaves (Durazo Herrmann, 2018;Gibson, 2013;Hiskey and Moseley, 2020;Mickey, 2015) and have suggested that pathways to subnational democratization are inherently different from those on the national level (Gibson, 2013).…”
Section: Subnational Democratization Literaturementioning
confidence: 99%
“…In the wake of this subnational turn, scholars have identified pockets of democracy in authoritarian countries (Gilley, 2010) and pockets of authoritarianism in democratic countries (Benton, 2017;Durazo Herrmann, 2010;Giraudy, 2015;Sidel, 2014). Moreover, they have analyzed the democratization of subnational authoritarian enclaves (Durazo Herrmann, 2018;Gibson, 2013;Hiskey and Moseley, 2020;Mickey, 2015) and have suggested that pathways to subnational democratization are inherently different from those on the national level (Gibson, 2013).…”
Section: Subnational Democratization Literaturementioning
confidence: 99%